Regulatory mechanism of circular RNA involvement in osteoarthritis - Zhang, Yuke; Liu, Liting; Liu, Kai; Wang, Meiying; Su, Xiulan; Wang, Jianzhong (Frontiers in Surgery, 2023)
Osteoarthritis (OA) causes joint pain, stiffness, and dysfunction in middle-aged and older adults; however, its pathogenesis remains unclear. Circular RNAs (circRNAs) are differentially expressed in patients with OA and participate in a multigene, multitarget regulatory network. CircRNAs are involved in the development of OA through inflammatory responses, including proliferation, apoptosis, autophagy, differentiation, oxidative stress, and mechanical stress. Most circRNAs are used as intracellular miRNA sponges in chondrocytes, endplate chondrocytes, mesenchymal stem cells, synoviocytes, and macrophages to promote the progression of OA. However, a small portion of circRNAs participates in the pathogenesis of OA by intracellular mechanisms, such as protein binding, methylation, or intercellular exosome pathways. In this sense, circRNAs might serve as potential novel biomarkers and therapeutic targets for OA.